2023
DOI: 10.3390/cancers15143637
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Promyelocytic Leukemia at Extremes of Age

Abstract: Tailored treatment with all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) has revolutionized the outcome of acute promyelocytic leukemia (APL) from a uniformly fatal disease to one of the most curable malignant diseases in humans. Due to its high efficacy, ATO/ATRA is the standard first-line therapy in younger adult, non-high-risk APL patients. However, early death is still a major issue in APL, particularly in older patients. Thus, rapid diagnostics, immediate access to ATRA-based therapy, and support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
(98 reference statements)
0
0
0
Order By: Relevance
“…This may suggest that patients with higher vulnerability to treatment toxicities may be allowed to continue receiving standard doses of these drugs if they survive early treatmentrelated mortality by reducing the drug dose. However, a small cohort analysis of elderly patients confirmed that suboptimal induction treatment with modified or reduced personalized approaches may lead to dismal outcomes [9]. Therefore, drugs such as venetoclax, a selective inhibitor of B-cell lymphoma 2 (BCL-2), which has been used successfully in the treatment of elderly patients with acute myeloid leukemia, may be worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that patients with higher vulnerability to treatment toxicities may be allowed to continue receiving standard doses of these drugs if they survive early treatmentrelated mortality by reducing the drug dose. However, a small cohort analysis of elderly patients confirmed that suboptimal induction treatment with modified or reduced personalized approaches may lead to dismal outcomes [9]. Therefore, drugs such as venetoclax, a selective inhibitor of B-cell lymphoma 2 (BCL-2), which has been used successfully in the treatment of elderly patients with acute myeloid leukemia, may be worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%